Organizational survival : profitable strategies for a sustainable future - Balestrero, Gregory (McGraw-Hill Education, 2014)
Presenting an airtight argument for sustainability being essential to any business strategy going forward; this book takes you step-by-step through the processes of developing a new strategy; or altering an existing one; to integrate sustainability into core business goals. --